2020
DOI: 10.1111/nmo.13887
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term neurophysiological effects of sensory pathway neurorehabilitation strategies on chronic poststroke oropharyngeal dysphagia

Abstract: Background Neurorehabilitation strategies for chronic poststroke (PS) oropharyngeal dysphagia (OD) have been mainly focused on the neurostimulation of the pharyngeal motor cortex with only marginal effects. In contrast, treatments targeting the PS oropharyngeal sensory pathway dysfunction offer very promising results, but there is little knowledge on the underlying mechanisms. We aimed to explore the neurophysiological mechanisms behind the effect of three sensory neurostimulation strategies. Methods We carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 43 publications
2
44
0
1
Order By: Relevance
“…Our group also has demonstrated the therapeutic effect of capsaicin at different concentrations and acute/subacute administration. Regarding the acute (single dose) treatment, we observed an improvement in time to LVC and UESO, reduction in the prevalence of oral and pharyngeal residue, and increased cortical excitability at a concentration of 150 μM but not at 10 −5 M [ 19 , 22 , 38 ]. The low dose showed better results when patients received the treatment over 10 days, three times a day.…”
Section: Discussionmentioning
confidence: 99%
“…Our group also has demonstrated the therapeutic effect of capsaicin at different concentrations and acute/subacute administration. Regarding the acute (single dose) treatment, we observed an improvement in time to LVC and UESO, reduction in the prevalence of oral and pharyngeal residue, and increased cortical excitability at a concentration of 150 μM but not at 10 −5 M [ 19 , 22 , 38 ]. The low dose showed better results when patients received the treatment over 10 days, three times a day.…”
Section: Discussionmentioning
confidence: 99%
“…Capsaicinoid ingestion also markedly reduced the prevalence of laryngeal penetration and pharyngeal residue in this study [ 44 ]. However, the acute ingestion of a lower dose (10 µM) of capsaicinoid-containing nectar boluses did not exert significant changes in swallowing events in chronic poststroke and older patients with oropharyngeal dysphagia [ 79 , 181 ], although it did increase the excitability of the motor cortex in response to pharyngeal electrical stimulation [ 181 ]. Another study reported that the acute application of red wine (without alcohol) or the polyphenols obtained from Cabernet Sauvignon grapes (used to make red wine) to the pharyngeal region led to reduced latencies of swallow responses in older patients with dysphagia associated with cerebrovascular diseases [ 182 ].…”
Section: Targeting Chemosensory Ion Channels To Improve Swallowingmentioning
confidence: 99%
“…22 Moreover, recent data show that strategies aiming to neurostimulate the sensory pathway cause an immediate improvement of the excitability of the motor cortex (pharmacological modulation with capsaicin and intra-pharyngeal electrical stimulation) and of the pharyngeal sensory conduction(rTMS). 23…”
Section: Discussionmentioning
confidence: 99%